The Influence of Wood Species and Type of Strands Arrangement to the Physical and Mechanical Properties of Oriented Strands Board - Nuryawan, Arif; Massijaya, Muh, Yusram; Hadi, Yusuf Sudo (Journal of Sylva Indonesiana, 2018)
This research was concerning in mat forming method for production of oriented strands board (OSB) in laboratory scale. There were three prototype models of OSB resulted in method applied, namely manually alignment’s model, using former device tool adopted from Nishimura’s model, and using former device made of plywood and wire’s model. From the physical and mechanical properties evaluation, the best mat of OSB was resulted in the third model, using former device made of plywood and wire.